Search for single top quark production in p p̄ collisions at √s = 1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2005)
We present a search for electroweak production of single top quarks in the s-channel and t-channel using neural networks for signal-background separation. We have analyzed 230 pb-1 of data collected with the DØ detector at the Fermilab Tevatron Collider at a center-of-mass energy of 1.96 TeV and find no evidence for a single top quark signal. The resulting 95% confidence level upper limits on the single top quark production cross sections are 6.4 pb in the s-channel and 5.0 pb in the t-channel. © 2005 Elsevier B.V. All rights reserved.